(untitled) (Bangladesh Journal of Botany, 2026)
Henan Province, China’s second-largest grain-producing region accounting for approximately 10% of national output, has pursued green agricultural transformation to balance food security with environmental sustainability. However, systematic prefecture-level evaluations remain limited. This study evaluates the Green Transition of Cultivated Land (GTCL) across 18 prefectures using panel data from 2000, 2010, and 2020. The GTCL index integrates Spatial Transition and Mode Transition. The provincial GTCL index increased from 0.41 to 0.52 (+27%), with substantial spatial heterogeneity. Hebi achieved the highest GTCL (0.68), followed by Jiaozuo (0.64), while Sanmenxia recorded the lowest (0.41). Four north-central prefectures emerged as green leaders with GTCL above 0.55. Critically, fertilizer intensity increased in all prefectures from 467 to 592 kg/ha (+26.8%), contrasting with national "zero growth" claims. Pesticide intensity decreased in 11 prefectures from 11.2 to 10.6 kg/ha (-5.4%). Grain yield increased from 4.86 to 6.27 t/ha (+29%). Water-saving irrigation correlated strongly with GTCL (r = 0.62) and yield (r = 0.63). Prefectures were classified into five types: green leaders, intensive conventional, degrading, low-input lagging, and mixed or stable. Differentiated policy recommendations include input reduction for intensive conventional prefectures, productivity enhancement for low-input lagging prefectures, and knowledge transfer from green leaders. Bangladesh J. Bot. 55(2): 269-278, 2026 (June)